Sideroxylon cochranei (Sapotoideae, Sapotaceae): a new cloud forest tree species from the Sierra de Manantlán and Cuale in western México - Vázquez-García, J. Antonio; Santana-Michel, Francisco J.; Cuevas-Guzmán, Ramón; Ortega-Peña, A. Salomé (Phytotaxa, 2021)
Sideroxylon cochranei (Sapotaceae) from Sierra de Manantlán and Cuale, in Jalisco, México is here described and illustrated. It is morphologically close to S. salicifolium, but it differs from the latter in being montane cloud forest trees versus sea-shore to lower montane tropical trees, also in having clustered leaves with longer petioles and sepals and larger fruits. A key to the species of Sideroxylon in western Mexico and a distribution map are provided. According to IUCN criteria, its conservation status was assessed as critically endangered (CR).